"Decision-making capacity for research participation among addicted people: a cross-sectional study". Issue 1 (December 2016) - Morán-Sánchez, Inés; Luna, Aurelio; Sánchez-Muñoz, Maria; Aguilera-Alcaraz, Beatriz; Pérez-Cárceles, Maria
Abstract Background Informed consent is a key element of ethical clinical research. Addicted population may be at risk for impaired consent capacity. However, very little research has focused on their comprehension of consent forms. The aim of this study is to assess the capacity of addicted individuals to provide consent to research. Methods 53 subjects with DSM-5 diagnoses of a Substance Use Disorder (SUD) and 50 non psychiatric comparison subjects (NPCs) participated in the survey from December 2014 to March 2015. This cross-sectional study was carried out at a community-based Outpatient Treatment Center and at an urban-located Health Centre in Spain. A binary judgment of capacity/incapacity was made guided by the MacArthur Competence Assessment Tool for Clinical Research (MacCAT–CR) and a clinical interview. Demographics and clinical characteristics were assessed by cases notes and the Mini-Mental State Examination, the Global Assessment Functional Scale and the Clinical Global Impression Scale. Results NPCs performed the best on the MacCAT–CR, and patients with SUD had the worst performance, particularly on the Understanding and Appreciation subscales. 32.7 % SUD people lacked research-related decisional capacity. There were no statistically significant differences between the groups in terms of capacity to consent to research. Conclusions The findings of our study provide evidence that a large proportion of individuals with SUD had decisional capacity for consent to research. It is therefore inappropriate to draw conclusions about capacity to make research decisions on the basis of a SUD diagnosis. In the absence of advanced cognitive impairment, acute withdrawal or intoxication, we should assume that addicted persons possess decision-making capacity. Thus, the view that people with SUD would ipso facto lose decision-making power for research consent is flawed and stigmatizing.